TRET-TET-TET 1987: THE FORMATION OF AWAY CULTURE AND THE IDENTITY OF PERSEBAYA SUPPORTERS - Pramudita, Agung; Athoillah, Ahmad (Satmata: Journal of Historical Education Studies, 2024)
The Tret-tet-tet activity in 1987 was an important moment that led to a change in the way football fans in Indonesia viewed their role. It also started the tradition of fans travelling to other cities to watch their home team play. This article exsplains how the Tret-tet-tet activity happened, the role of important people, and how a new cultural identity emerged among Persebaya supporters after the activity. To do this, we used a historical method and historical sources like newspapers, magazines, literary works, and interviews. This study found that the Tret-tet-tet activity occurred because it was inspired by supporters from the West, support for the Persebaya club competing in the 1987 final, mobilization carried out by Jawa Pos, the role of Jawa Pos’s boss Dahlan Iskan, and the new identity of football supporters. The study found that the Tret-tet-tet activity has become a new tradition in the management of supporters in Indonesia based on the support of the mass media and the emergence of a new culture of soccer supporters.